Study on Fast Codeword Search Based on Improved Ant Colony Algorithm - Zou, Da Yong; Wu, Wei (Applied Mechanics and Materials, 2014)
Vector quantization technology is an efficient and competitive method for data compression, but it is not easy to be implemented because of the comparatively high computation complexity it requires during the coding and decoding process. This paper presents a method of Dual Population Ant Colony Algorithm Codeword Quick Search (DPACAS), exploiting the mechanism of ant trace the optimal path through the pheromones remained, and the behavior pattern of making objects together by picking up and putting down them. It uses Parallel Ant Colony algorithm to sufficiently accelerate the convergence of the ant colony. When the scale of the codebook becomes larger, by setting parameters reasonably and exchanging the pheromones between two species, it broadens the search space, reduces the search time and improves the algorithmic global convergence effectively.